Valutazioni economiche di atorvastatina in prevenzione secondaria: un aggiornamento - de Portu, Simona; Montella, Sabato; Cortesi, Paolo; Menditto, Enrica; Cammarota, Simona; Citarella, Anna; Mantovani, Lorenzo G. (Farmeconomia. Health economics and therapeutic pathways, 2011)
Introduction: cardiovascular diseases are the most common reason of mortality and morbidity in the world, despite therapeutic interventions have improved patients’ prognosis in the last decades. Aggressive lipid lowering treatment with atorvastatin has demonstrated to be effective in preventing the occurrence of new cardiovascular events requiring hospitalizations, in patients previously affected by coronary syndromes. However, the increasing costs of managing cardiovascular diseases impose a careful analysis of the economic benefits of these therapies. Objective: to assess the economic sustainability of using atorvastatin for the secondary prevention of cardiovascular events. Material and Methods: we derived clinical information from five randomized, multicenter trials (AVERT, IDEAL, MIRACL, PROVE-IT, TNT) evaluating efficacy and tolerability of high dosage treatment with atorvastatin over control groups in different patient populations and for different follow up periods. A costeffectiveness analysis in the perspective of the NHS has been performed, under the hypothesis of the imminent price reduction of atorvastatin, due to the loss of exclusivity. Results: in trials AVERT, MIRACL, PROVE IT, the treatment with atorvastatin has demonstrated to reduce both cardiovascular events and overall healthcare direct costs, compared to the respective control groups. In trials IDEAL and TNT, the therapy with atorvastatin has resulted to be cost effective, with incremental cost-effectiveness ratio respectively of € 6,310 for avoided event (vs simvastatin 10 mg) and € 9,058 for CV disease free patient (vs atorvastatin 10 mg). Discussion: the present study represents an update of previous cost-effectiveness analyses, which have previously evaluated the economic consequences of using atorvastatin for the secondary prevention of cardiovascular events. The present analysis has proved the economic benefits deriving from the usage of atorvastatin, which is a dominant alternative in the AVERT, MIRACL and PROVE-IT clinical settings, and a cost effectiveoption in the IDEAL and TNT study populations.